Social Dimension in The Novel Kita Pergi Hari Ini and Its Integration in Character-based Literature Learning in SMA - Swandari, Fayza; Maruf, Ali Imron Al (Universitas Muhammadiyah Surakarta, 2023)
This research was conducted with the aim of describing (1) the social dimension in the novel Kita Go Hari Ini by Ziggy Zezsyazeoviennazabrizkie and (2) its integration in character-based literature learning in high school which is adapted to the Learning Outcomes of Indonesian Language subjects in Phase F in the Merdeka Curriculum. This research uses a qualitative descriptive method by presenting the results in the form of descriptions where the data is collected using documentation techniques. Data analysis was carried out using the dialective method. The data source is the novel Kita Go Hari Ini with data in the form of story quotes in the novel that represent the social dimension. The research results show that: (1) the social dimensions of the novel include high birth rates, problems with ruling groups, bad environments for children, misunderstanding of children's intelligence, poverty, and stereotypes of femininity and masculinity and (2) the research results are integrated with literature learning in high school by implementing literary appreciation material into teaching materials using the discovery learning model. Introduction Section